2020
DOI: 10.1186/s13104-020-05187-y
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of plasma calretinin in patients with malignant pleural mesothelioma

Abstract: Objective: Calretinin is a well-known immunohistochemical tissue marker in the diagnosis of malignant mesothelioma. Promising results also indicate the use in early detection. In the present cross-sectional survey, correlations of calretinin plasma levels with clinical features were investigated. Plasma samples of 60 patients with malignant pleural mesothelioma (MPM) and 111 cancer-free controls formerly exposed to asbestos were compared. Calretinin concentrations were determined in plasma using an enzyme-link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 21 publications
(29 reference statements)
2
6
0
Order By: Relevance
“…At the cutoff value of 0.32 ng/mL, the specificity was high (89%), while the sensitivity was limited (68%). Consistent with our results, other studies to date have shown that patients with MM have higher levels of calretinin than other subjects who were also exposed to asbestos [ 8 , 21 , 30 ], suggesting calretinin behaves similarly to mesothelin and other biomarkers [ 30 ]. Similar plasma calretinin cutoff values were observed in previous studies [ 8 , 23 ], while higher cutoff values were required to reach 95% or 98% predefined specificity [ 8 , 30 ], similar to our study.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…At the cutoff value of 0.32 ng/mL, the specificity was high (89%), while the sensitivity was limited (68%). Consistent with our results, other studies to date have shown that patients with MM have higher levels of calretinin than other subjects who were also exposed to asbestos [ 8 , 21 , 30 ], suggesting calretinin behaves similarly to mesothelin and other biomarkers [ 30 ]. Similar plasma calretinin cutoff values were observed in previous studies [ 8 , 23 ], while higher cutoff values were required to reach 95% or 98% predefined specificity [ 8 , 30 ], similar to our study.…”
Section: Discussionsupporting
confidence: 92%
“…We found that the concentration of calretinin was higher in women and a higher cutoff value was required to differentiate between MM patients and other subjects; however, the sensitivity was lower. This confirmed the results of other studies that also found higher levels of calretinin in small groups of women [ 21 , 24 ], except in one study evaluating plasma calretinin in a very small cohort of women from the Mexican population [ 23 ]. Other previous studies only evaluated calretinin levels in male subjects.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Consistent with previous studies, higher calretinin mRNA expression was associated with longer OS in the TCGA MESO cohort. So far, the association between tissue calretinin expression and soluble calretinin in MM was only investigated in one study: patients with calretinin-positive tumors had higher plasma calretinin [ 29 ], and, therefore, a similar prognostic role in tissue and blood could be expected. However, the positive correlation of calretinin expression in tissue and plasma could be attributed to the fact that calretinin is more often detected in epithelioid and biphasic MM compared to the sarcomatoid subtype in both tissue and plasma or serum of MM patients [ 18 , 20 , 30 , 31 ].…”
Section: Discussionmentioning
confidence: 99%